UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INGGRIS MELALUI METODE PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS XI.IPS.3 SMAN 1 PASAMAN - Yosniferi Yosniferi (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on the results of student learning XI.IPS.3 Class SMAN 1 Pasaman in the subjects of English sub-Revealing the meaning of the essay by us- ing variety of oral language accurately, fluently and acceptable in the context of everyday life in text form: narrative, spoof, and hortatory exposition.ditemukan that results for students in the subjects of English sub-Revealing the meaning of the essay by us- ing variety of oral language accurately, fluently and acceptable in the context of everyday life in text form: narrative, spoof, and hortatory exposition.masih very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in the subjects of English sub Revealing-kan meaning in essay by us- ing variety of oral language accurately, fluently and acceptable in the context of everyday life in text form: narrative, spoof, and hortatory exposition through Discovery Learning method Learning in Class XI.IPS.3 SMA N 1 Pasaman West Pasaman.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 30 students Grades XI.IPS.3 People SMA N 1 Pasaman. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the method of Learning Discovery Learning can improve student learning outcomes in the subjects of English sub Revealing-kan meaning in essay by us- ing variety of oral language accurately, fluently and acceptable in the context of life daily in text form: narrative, spoof, and hortatory exposition.di SMA N 1 Pasaman. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 50.8 (Self) increased to 84.73 (good) with an increase of 33.93%.